Assessment of contemporary muslim Saudi visual artists' satisfaction in practising visual arts - Turkestani, Nahed Mohammed Mosa (Kulliyyah of Architecture and Environmental Design,International Islamic University Malaysia, 2015)
This thesis is concerned with the impact of social factors affecting the satisfaction levels of contemporary Muslim Saudi visual artists (CMSVA). Satisfaction is a strong predictor of overall individual well-being. Although satisfaction level has been subjected to increased scrutiny in recent years, Muslim visual artists' satisfaction levels have received only slight attention in the literature. This study examines how social factors influence the satisfaction levels of CMSVA. This naturally includes understanding the relationships between the concerned social factors. To achieve this, we develop a comprehensive model and empirically test several social factors affecting CMSVA' satisfaction. The results from such an analysis will assist in effectively planning approaches to the social and artistic empowerment of CMSVA in the advancement of their careers and the preservation of the artistic identity and integrity of Saudi culture, history, and society. This is the first attempt to identify social factors affecting CMSVA's satisfaction level in producing visual art and distinguishing the relationship between the social factors affecting CMSVA' satisfaction level. The research data were collected by means of a survey through personal interviews and a structured questionnaire. Out of 500 targeted respondents, 265 questionnaires were deemed usable for statistical analysis. Statistical tests were performed using statistical procedures of SPSS version 17 and AMOS version 20. The main statistical techniques used included exploratory factor analysis (EFA), the Levene test for homogeneity of variances (ANOVA) and confirmatory factor analysis (CFA) - Structural Equation Modeling (SEM). The current research provides significant academic insights and managerial implications and contributes to knowledge in the field of visual art research. The finding confirms that knowledge in Saudi Arabia was one of the social factors positively affecting contemporary Muslim Saudi visual artists' satisfaction level. We also demonstrated that social and institutional support, environmental effects, audiences, travel and financial abundance can be effective in CMSVA' satisfaction level along with social accomplishment, personal accomplishment and enhancement as fundamentals of satisfaction. Hence, to improve CMSVA' satisfaction level, social factors in the Kingdom of Saudi Arabia especially knowledge must be studied and examined. The current research demonstrates that the acceptance of the unified model of social factors affecting CMSVA' satisfaction level established in the Muslim Saudi culture may be transferred to other cultures although with varying degrees of difference. Assessing the satisfaction level of CMSVA helps to enhance their status, eventually leading to improved contemporary Muslim Saudi visual art.